2022
DOI: 10.3390/su14063646
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Similarity of the Situation in the EU Labour Markets and Their Changes in the Face of the COVID-19 Pandemic

Abstract: The aim of the study is to assess the similarity of the situation in the EU labour markets and their evolution using selected indicators in the period before and during the COVID-19 pandemic. The benchmark are the countries that most closely meet the Sustainable Development Goals related to the labour market. We use quarterly data from Eurostat presenting the basic indicators of the labour market: unemployment, employment, and activity rates. We analyse all indicators for the total population, young people, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 75 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…As a result, the obtained data supports the conclusions of other studies. The benchmarking conducted for the European Union's labour market [42] before and during COVID-19 noted the same negative effect. For example, in Sweden, Belgium, Canada, the United States, and Chile, COVID-19 has been shown to have a negative impact on non-standard work hours, and [44,45] identified a job loss in the aviation industry along a similar line.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…As a result, the obtained data supports the conclusions of other studies. The benchmarking conducted for the European Union's labour market [42] before and during COVID-19 noted the same negative effect. For example, in Sweden, Belgium, Canada, the United States, and Chile, COVID-19 has been shown to have a negative impact on non-standard work hours, and [44,45] identified a job loss in the aviation industry along a similar line.…”
Section: Discussionmentioning
confidence: 70%
“…Another dimension of employment fluctuation in the short term is that employment behaviour might receive many shocks that have different origins, such as economic [30,31], social [32], political [33], technological [34], and input cost shocks [35,36], as well as health shocks related to viral epidemics, e.g., the current crisis caused by COVID-19 [1, [37][38][39][40]. As they take lessons from ancient employment shocks during previous recessionary periods [41], researchers are interested in examining the influence of COVID-19 on employment by benchmarking the periods before the pandemic vs. the era ofCOVID-19 [42], as they have learned from earlier recessionary periods [41]. In fact, [43] emphasizes the COVID-19 pandemic's effects on flexible work relationships and careers to examine how they might be affected by it, its recurring consequences, and its impact on flexible employment relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Recovery from the virus occurs in different ways and at different times in the market (Enfield, 2021). In post-Covid Europe, the situation varies from country to country due to different economic and social developments (Bieszk-Stolorz & Dmytrów, 2022). Research analyzing the labour market in the aftermath of the pandemic shows that companies are experiencing a downward trend in supply and a shortage of highly qualified workers.…”
Section: Labour Marketmentioning
confidence: 99%
“…Therefore, there is no doubt that crises of all kinds, especially those of a global nature, pose a threat to the achievement of SDGs. Preliminary research on the EU labour market (SDG 8.5, SDG 8.6) from the years 2018-2021 showed that the COVID-19 pandemic did not affect the similarities of the labour markets in the EU countries, but rather influenced the similarities of changes in those markets (Bieszk-Stolorz & Dmytrów, 2022).…”
Section: Introductionmentioning
confidence: 99%